The exorcism of art - Work, Robert J., author; Ellerby, David A., advisor; Twarogowski, Leroy A., committee member; Coronel, Patricia D., committee member; Pratt, John Clark, committee member (Colorado State University. Libraries, 1999)
My thesis is based on my connections with primitive art. The significant form in primitive art is addressed by Clive Bell. His writings have supported my own belief that early humans derived their art from a fear-based reverence for nature. The energy that has been perceived by viewers in my work is a result of the panic I experienced in approaching the surface and subject. This has been true whether the works are seen as abstract, nonrepresentational, or narrative. This is why I see my work as an exorcism--an exorcism of the feared forces of the unknown. I respond to my immediate environment and those in it intuitively, realizing that we are a part of nature rather than apart from it. My art is quest seeking my own origin. It is a quest to a creator that may not recognize his creation.
Keywords: Painting -- Themes, motives; Symbolism in art